A pedagogic method helps to create an actionable policy from big data through a PDCA cycle. (2016) - Koh, Wook; Choi, Jaewon
Big data and learning analytics for higher education is a rapidly growing field with disruptive potential. However, there has been little research reported on a pedagogic method that helps to create an actionable policy from big data. In recent years, there is a meaningful debate that big data alone cannot improve teaching, and more research is needed from a pedagogic point of view. We, therefore, developed a pedagogic method called BDAL (big data for active learning) that helps to create an actionable policy through a PDCA (plan-do-check-act) cycle. It facilitates students to examine their goals and motivations, to improve learning styles, and to be an active learner. An experiment was conducted on 556 undergraduate students for a control group and an experimental group. With the help of BDAL, we were able to gain an actionable policy to improve education further both in and out of classrooms.